Tilapia Fish Feed Formulation To Improve Feed Quality In The Kedungpandan Jabon Sidoarjo Fish Cultivator Group: Formulasi Pakan Ikan Nila Untuk Peningkatan Kualitas Pakan Pada Kelompok Pembudidaya Ikan Kedungpandan Jabon Sidoarjo - Anshory, Izza; Fachrudin, A’rasy; Lukman , Lukman (Universitas Muhammadiyah Sidoarjo, 2022)
Fish farmers who are members of the Gelondoro fish cultivator farmer group, Kedungpandan Jabon Sidoarjo village, utilize the main food source, namely aquatic plants that grow naturally in pond ponds and buy fish feed pellets from the factory as additional food for the tilapia they cultivate. The problem is, the number of aquatic plants that grow in pond ponds is limited and the price of fish feed pellets is expensive. The purpose of this community service activity is to provide knowledge about the formulation of fish feed pellets containing correct and appropriate nutrients for partners. The method used in this community service activity is to calculate the formulation of tilapia feed with a protein content of 45% for the needs of 15 kg of feed ingredients. The results of the activity showed that the rice bran, wheat, and corn flour needed for each ingredient was 873 grams. Meanwhile, for anchovy, snail and soybean meal, 4,125 grams of each ingredient are required. The formulation has resulted in the composition of ingredients for nutrition which is determined at 45% for 15 kg of fish pellets.